Credit-constrained in risky activities? The determinants of capital stocks of micro and small firms in Western Africa - Michael Grimm; Simon Lange; Jann Lay (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
Micro and small enterprises (MSEs) in developing countries are typically considered to be severely credit constrained. Additionally, high business risks may partly explain why capital stocks of MSEs remain low. This article analyzes the determinants of capital stocks of MSEs in poor economies focusing on credit constraints and risk. The analysis is based on a unique, albeit cross-sectional but backward-looking, micro data set on MSEs covering the economic capitals of seven West-African countries. The main result is that capital market imperfections indeed seem to explain an important part of the variation in capital stocks in the early lifetime of MSEs. Furthermore, the analyses show that risk plays a key role for capital accumulation. Risk-averse individuals seem to adjust their initially low capital stocks upwards when enterprises grow older. MSEs in risky activities owned by wealthy individuals even seem to over-invest when they start their business and adjust capital stocks downwards subsequently. As other firms simultaneously suffer from capital shortages, such behaviour may imply large inefficiencies.
Keywords: D13; D61; O12; 330; Informal sector; micro and small enterprises; credit constraints; risk; risk aversion; firm growth; West-Africa